Understanding The Dynamics And Challenges Of Learning In Groups Of Students In Grade Vii Mts Yapdi On Procedure Text Material - Liza Handayani Batu Bara; Ewin Sanjaya Gajah; Nisa Hafzhiyah Hasibuan; Suci Rahmadani; Elfina Wety; Nursamsia Rambe; Mutia Asmi Fadillah (Journal Analytica Islamica, 2024)
This study aims to identify and analyze the difficulties and obstacles of class VII students of MTs YAPDI in group learning of procedural text material. This qualitative study used observation, interview, and documentation techniques to collect data from 22 students (saturated sample). Data analysis used descriptive analytic with the Huberman and Miles model (collection, reduction, display, and verification of data). The findings of the study showed several difficulties, namely: (1) differences in understanding of the material between members, (2) lack of member participation, (3) communication problems in groups, (4) lack of motivation and responsibility, (5) lack of self-confidence, and (6) conflict between members. It is recommended that further research focus on developing interventions to overcome these difficulties, the role of teachers in facilitating group learning, and the impact of learning methods on group dynamics and learning outcomes of procedural texts.